1997
DOI: 10.1046/j.1469-8137.1997.00634.x
|View full text |Cite
|
Sign up to set email alerts
|

Purification and characterization of a β‐1,4‐endoxylanase from the ericoid mycorrhizal fungus Hymenoscyphus ericae

Abstract: SUMMARYA yj-l,4-endoxylanase from the ericoid mycorrhizal fungus H. ericae has been purified to electrophoretic homogeneity using isoelectric focusing, ion exchange and gel permeation chromatography. The enzyme has an isoelectric point of 4-85-5-20 and a molecular weight of 58-4 kDa. The apparent S^.^ of the enzyme for soluble birchwood glucuronoxylan is 375 mg ml'^ and the V^^^ 468-0 nkatal mg"* protein. The pH optimum for activity is 4-5 and that for stability is 3-5^-O; these values are discussed in the con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
2

Year Published

2003
2003
2021
2021

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 48 publications
0
10
2
Order By: Relevance
“…Nevertheless, compared with these activities, A. zeae EA0802 culture with corn straw or oat spelt xylan produced smaller xylanase activity of 0.76 UmL −1 , on ninth day and 1.56 UmL −1 after 15 days of growth, respectively (Table 1). Hymenoscyphus ericae, an endophyte fungus, produced two xylanase forms, with a total activity of 5.8 UmL −1 , in liquid medium with oat spelt xylan [48]. Rhizopus oryzae produced 0.39 U mL −1 using 1% xylan as carbon source after 6 days, and when 2% corn cob was used, the fungi produced 2.8 UmL −1 after 5 days [49].…”
Section: Xylanasementioning
confidence: 99%
“…Nevertheless, compared with these activities, A. zeae EA0802 culture with corn straw or oat spelt xylan produced smaller xylanase activity of 0.76 UmL −1 , on ninth day and 1.56 UmL −1 after 15 days of growth, respectively (Table 1). Hymenoscyphus ericae, an endophyte fungus, produced two xylanase forms, with a total activity of 5.8 UmL −1 , in liquid medium with oat spelt xylan [48]. Rhizopus oryzae produced 0.39 U mL −1 using 1% xylan as carbon source after 6 days, and when 2% corn cob was used, the fungi produced 2.8 UmL −1 after 5 days [49].…”
Section: Xylanasementioning
confidence: 99%
“…Cellobiose was also used as a carbon source in each isolate tested. Cellobiose can be transported directly or following cleavage into glucose molecules via an extracellular cellobiase before absorption (Griffin, 1994;Burke and Cairney, 1997).…”
Section: Carbonmentioning
confidence: 99%
“…However, there are few studies reported on utilization of plants as sources of endophytic xylanase producer (Burke andChairney 1997, Suto et al 2002) and no work presented on xylanolytic endophyte isolation from maize. This is the first report presenting the screening of maize for xylanolytic bacteria isolation.…”
Section: Xylanolytic Microorganism Isolationmentioning
confidence: 99%
“…Due to hemicellulosic (xylan) component of plant cell wall, existence of endophytic xylanolytic microorganisms is expected. Few endophytic xylanase producers have been reported up to date (Burke et al 1997, Suto et al 2002, Ersay ı n et al 2007.…”
Section: Introductionmentioning
confidence: 99%